Anthropometric measures in Bangladeshi schoolchildren to determine body composition and nutritional status: a descriptive cross-sectional study - Rahman, Sharmin; Khan, Mohammad Adnan; Anam, Md Rifat; Nahar, Yesmin; Ara, Shamim (International Journal Of Community Medicine And Public Health, 2022)
Background: The development of improved health and nutrition in adulthood is significantly influenced by early nutrition. It is, however, almost ever investigated how to determine the nutritional condition of Bangladeshi children using anthropometric measurements including height, weight, biepicondylar width of the humerus and femur, BMI, and BSA. Methods: A descriptive cross-sectional study was conducted among 400 government elementary school students aged between 9 and 12 years in Dhaka, Bangladesh. Data was collected using a semi-structured questionnaire and analyzed using SPSS. Results: For the B1 and B2 groups, heights ranged from 124.00 to 151.00 cm and 129.00 to 157.00 cm, respectively. Height ranges for the C1 and C2 groups were respectively 129.50-153.00 cm and 129.00-160.00 cm. The B2 study group had a greater weight than the B1 study group (p<0.001), where C2 was heavier than the C1 research group (p<0.001). The A1 study group's biepicondylar width of the humerus was greater than the A2 study group's (p<0.05) and biepicondylar humerus width was greater in the B2 study group compared to the B1 study group (p<0.05). On the other hand, the B1 study group's biepicondylar femur width was higher than the B2 study group (p<0.05). The B2 group's body surface area was larger than the B1 study group's (p<0.001) and body surface area of C2 group was greater than C1 study group (p<0.001). Conclusions: Analyses of body composition and anthropometric measurements suggest that children and adolescents' nutritional status was below the reference requirement, according to the results of the current study.